Carex panduranganii, a new name for Carex nilagirica Viji, Pandur., Deepu & G.C. Tucker (Cyperaceae) - Kalidass, Chinnamadasamy (Phytotaxa, 2016)
Carex Linnaeus (1753: 972) is one of the largest genera of angiosperms with more than 2000 species in the world (Reznicek 1990, Goetghebeur 1998). In India, Karthikeyan et al. (1989) and Prasad & Singh (2002) reported 160 species, 1 subspecies and 29 varieties. Recently, Viji et al. (2016) recorded a new species from Tamil Nadu which is new to the Indian flora, namely Carex nilagirica Viji, Pandur., Deepu & G.C. Tucker (2016: 1). However, there is another Carex nilagirica published by Hochst ex Steudel (1855: 207), which is currently treated as a heterotypic synonym of Carex filicina Nees (1834: 123). As a result, and under the International Code of Nomenclature for algae, fungi and plants (McNeill et al. 2012), the name Carex nilagirica Viji, Pandur., Deepu & G.C. Tucker is illegitimate, as it is a later homonym of Carex nilagirica Hochst ex. Steud. (Art. 53.1). Therefore, a new name Carex panduranganii is proposed as a replacement name for Carex nilagirica Viji, Pandur., Deepu & G.C. Tucker.